DESCRIPTION OF POST SECTIO CAESAREA PATIENTS WITH CONVENTIONAL METHODS AND ERACS METHODS - Dian Taviyanda; Kili Astarani; Rimawati; Emiliana Nyitiyas Wulan (Universitas STRADA Indonesia, 2024)
hysterotomy) through an incision in the front abdominal wall. The problem that often arises in post Section Caesarea patients is pain that is still felt 2-3 days after Sectio Caesarea so that it makes the mother reluctant to move her body. The purpose of this research is to describe the pain level of post section caesarea patients by conventional method and ERACS method in Melati Room at Immanuel Way Halim Bandar Lampung Hospital.The design of this research is descriptive research. The population of this study were conventional post-cesarean section patients and in patients with the ERACS method. The number of samples was 48 patients, 36 conventional post section caesarea patients and 12 post-caesarean patient with the ERACS method. This reseach used accidental sampling.